Seroprevalence of SARS-CoV-2 in four states of Nigeria in October 2020: A population-based household survey. - Rosemary A Audu; Kristen A Stafford; Laura Steinhardt; Zaidat A Musa; Nnaemeka Iriemenam; Elsie Ilori; Natalia Blanco; Andrew Mitchell; Yohhei Hamada; Mirna Moloney; Emem Iwara; Alash'le Abimiku; et al. (Public Library of Science (PLoS), 2022)
The observed epidemiology of SARS-CoV-2 in sub-Saharan Africa has varied greatly from that in Europe and the United States, with much lower reported incidence. Population-based studies are needed to estimate true cumulative incidence of SARS-CoV-2 to inform public health interventions. This study estimated SARS-CoV-2 seroprevalence in four selected states in Nigeria in October 2020. We implemented a two-stage cluster sample household survey in four Nigerian states (Enugu, Gombe, Lagos, and Nasarawa) to estimate age-stratified prevalence of SARS-CoV-2 antibodies. All individuals in sampled households were eligible for interview, blood draw, and nasal/oropharyngeal swab collection. We additionally tested participants for current/recent malaria infection. Seroprevalence estimates were calculated accounting for the complex survey design. Across all four states, 10,629 (96·5%) of 11,015 interviewed individuals provided blood samples. The seroprevalence of SARS-CoV-2 antibodies was 25·2% (95% CI 21·8-28·6) in Enugu State, 9·3% (95% CI 7·0-11·5) in Gombe State, 23·3% (95% CI 20·5-26·4) in Lagos State, and 18·0% (95% CI 14·4-21·6) in Nasarawa State. Prevalence of current/recent malaria infection ranged from 2·8% in Lagos to 45·8% in Gombe and was not significantly related to SARS-CoV-2 seroprevalence. The prevalence of active SARS-CoV-2 infection in the four states during the survey period was 0·2% (95% CI 0·1-0·4). Approximately eight months after the first reported COVID-19 case in Nigeria, seroprevalence indicated infection levels 194 times higher than the 24,198 officially reported COVID-19 cases across the four states; however, most of the population remained susceptible to COVID-19 in October 2020.